The Influence of Competence and Work Environment With Discipline as an Intervening Variable on Teacher Performance at SMK Negeri 2 Jambi City - Harmonis, Harmonis; Yamali, Fakhrul Rozi; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe the competence, work environment, discipline and performance of teachers at SMK Negeri 2 Jambi City. Then to analyze the influence of competence and work environment on discipline, analyze the influence of competence and work environment on teacher performance, then analyze the influence of discipline on teacher performance, then analyze the influence competence and work environment through discipline towards teacher performance. This research is a research using descriptive and verifiative research methods, which is a method in examining a group of people, an object, situation and condition of a system of thought with a goal to make a description, a systematic picture according to the facts being investigated. The verification research aims to test hypotheses about the influence between variables of this study. This research involved teachers at SMK Negeri 2 Jambi City totaling 132 people. A sample of 57 respondents based on the formula of the Probability Sampling technique. Data was analyzed using SPSS.22. The results showed that competence in good condition, work environment in good condition, high discipline and high teacher performance, that competence and work environment simulatively or partially have a positive and significant effect on discipline , competence and work environment simultaneously and partially have a positive and significant effect on teacher performance, and discipline has a positive and significant effect on teacher performance at SMK Negeri 2 Jambi City .